Media Political Coup: Communication Strategy, Freedom of Speech Law on Digital Platforms in the 2024 Presidential Election - Hermawan, Vera (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The 2024 Presidential Election (Pilpres) in Indonesia marks a new chapter in the dynamics of political communication, which is increasingly shifting into the digital realm. Social media has become not only a campaign tool but also an arena for an intense and systematic battle over political narratives. This study aims to analyze the phenomenon referred to as a media political coup, namely the domination and control of digital space by political actors through structured communication strategies, and to evaluate the legal regulations governing freedom of speech on digital platforms. Using a qualitative social research method, this study examines how digital communication strategies are implemented in political contests and how policies such as the Electronic Information and Transactions Law (UU ITE) and regulations issued by the Ministry of Communication and Information Technology (Kominfo) affect citizens’ freedom of expression. The results show that the digital space during the 2024 Presidential Election has become a central arena for shaping public opinion through intensive and structured strategies employed by political actors. The massive use of social media, digital algorithms, and buzzer networks has led to the dominance of certain narratives, even to the point of displacing critical opposing discourses. In addition, the misuse of ambiguously interpreted articles within the UU ITE to silence criticism and restrict freedom of expression has had a negative impact on the quality of democracy. Therefore, there is a need to strengthen digital literacy among the public and update regulations to ensure that democracy in the digital era is maintained fairly and transparently